Regulation of Area and Abandoned Land in Indonesia - KMS Herman (Faculty of Law, Universitas Pekalongan, 2021)
The existence of no-man's land is still a thorny issue, and the resolution process seems delayed. Even though the 1945 Constitution (UUD 1945) as the UUD and LEGAL No. 5 of 1960 mentions the Agrarian Rights LAW (UUPA) as its articles, don't let land production stop in Indonesia. Management of Territorial Areas and No-Man's Land, according to the law it is used to protect land and areas that may not be owned (PP No. 20 of 2021). The goal of this study is to single out the regulation of no-man's land in law and land management and to discuss the process of determining which land is now officially a no-man's land according to Government Law 20 of 2021, which regulates the administration of permits. Territory and land. This research is legal research that uses legal documents by using the law and its context. The source of legal information for this research is from legal documents, namely PP Number 20 of 2021, supported by secondary sources, namely legal books and newspapers that are relevant to this research. The research results found that Federal Law No. 20 of 2021 that Unclaimed Land is privately owned land, land with Administrative Law, and land acquired by the Ministry of Land, which is intentionally left uncultivated, unused, and/or not maintained. The country is deliberately not used in accordance with its nature or status; if the land is not used for permit purposes; The country is not good.